1990
DOI: 10.1136/jnnp.53.7.597
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairments and depression in Parkinson's disease: a follow up study.

Abstract: The presence of depression and cognitive impairments was examined in seventy patients with Parkinson's disease (PD). Forty nine patients of this original cohort were re-examined between three and four years after the first evaluation. While both depressed and non-depressed patients showed a significant decline in cognitive function during the follow up period, intellectual decline was significantly more severe for the depressed group. Depressed patients also showed a faster rate of progression of motor signs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
2
13

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(77 citation statements)
references
References 27 publications
7
55
2
13
Order By: Relevance
“…Furthermore, the presence of severe cognitive deterioration seems to be accompanied by a decreased life expectancy. This finding is in agreement with other recent studies reporting that dementia in parkinsonian patients alters the prognosis and reduces survival [31][32][33][34], The nat ural history of parkinsonian dementia therefore does not seem to be any different than the history of other forms of progressively disabling degenerative dementia [35].…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the presence of severe cognitive deterioration seems to be accompanied by a decreased life expectancy. This finding is in agreement with other recent studies reporting that dementia in parkinsonian patients alters the prognosis and reduces survival [31][32][33][34], The nat ural history of parkinsonian dementia therefore does not seem to be any different than the history of other forms of progressively disabling degenerative dementia [35].…”
Section: Discussionsupporting
confidence: 82%
“…A relationship between motor severity [25][26][27][28][29] and depression [26,30,31] has been demonstrated in other studies of dementia in PD. Depression is common in PD [32,33] and it is possible that depression may coexist with dementia rather than exert a negative effect upon it.…”
Section: Discussionmentioning
confidence: 93%
“…Conversely a previous review yielded only two studies with conflicting results. The early one did not find an association between depression and survival in PD 12 , whereas Hughes et al 13 , reported that depressed PD patients presented a 1.64 (CI 1.26-2.99) risk of death as compared to controls. In order to provide more information on this issue, the aim of this study is to evaluate the survival rate in a cohort of PD patients with and without depression.…”
Section: Introductionmentioning
confidence: 94%